2009
DOI: 10.1142/s0219581x09005840
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Simulation and Experiment Using Uv Curable Gap Fill Materials for Global Planarization

Abstract: This study focuses on the correlation between simulation and experiment using UV curable gap fill materials for global planarization in advanced lithographic and nanoimprinting techniques. A novel gap fill material has been optimized and developed for global planarization properties. Gap fill materials planarize irregular substrates such as patterned steps, vias, and trenches to increase depth of focus and patterning resolution. After planarizing the substrate surface, the gap fill materials provide dry etchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…A stripping test result of less than 10 nm was considered acceptable. [17][18][19][20] The stripping test showed no detectable changes (less than 1.0 nm) in 300 nm film thickness of NCI-NIL-R01 and 100 nm film thickness of NCI-NIL-U01, indicating that NCI-NIL-R01 and NCI-NIL-U01 do not interact significantly. It was obvious that these materials were crosslinked in terms of resistance.…”
mentioning
confidence: 94%
“…A stripping test result of less than 10 nm was considered acceptable. [17][18][19][20] The stripping test showed no detectable changes (less than 1.0 nm) in 300 nm film thickness of NCI-NIL-R01 and 100 nm film thickness of NCI-NIL-U01, indicating that NCI-NIL-R01 and NCI-NIL-U01 do not interact significantly. It was obvious that these materials were crosslinked in terms of resistance.…”
mentioning
confidence: 94%
“…A stripping test result of less than 10 nm indicated that the film was sufficiently crosslinked and this was considered acceptable. 19,20)…”
Section: Stripping Testmentioning
confidence: 99%
“…The highest resolution patterning was demonstrated by Willson at the University of Texas, 1) and by Sakai,2) and Liang et al 3) Multiple spinon planarizing materials for lithography have been also reported. [4][5][6] For advanced nanoimprint lithography, [7][8][9][10][11][12][13][14][15][16][17] however, further technical progress is required in resist pattern peeling, generated defects, process throughput, and the manufacture of high-resolution templates. On these issues, we have developed a new hard mask material with methacrylate side groups in siloxane polymer to obtain a wider imprinting margin, higher regional planarization on…”
Section: Introductionmentioning
confidence: 99%